Manejo do crescimento das plantas matrizes de morangueiro na produção de pontas de estolão - Dal Picio, Miriane (2013)
The main objective of this thesis was to deep knowledge about dry matter partitioning among the strawberry stock plant and stolons and daughters plants in order to determine management criteria for maximizing the production of runner tips in the good time for saling plug plants. Two experiments were conducted inside a polyethylene umbrella greenhouse, at Departamento de Fitotecnia, UFSM, using the cultivar Camino Real. The stock plants were planted in pots filled with the organic substrate Mecplant® HF and fertigated by drippers. The experimental design in both experiments was a completely randomized split plot design with four replications of three plants. In the first experiment planting was done on October 14th, 2010 and final plant harvest was on March 28 th, 2011. In this experiment treatments were two source levels, respectively unshaded and shaded mother plants, and four sinks levels: runner tips were collected weekly (1) and monthly (2), rooting runner tips to originate four daughter plants (3) and four unrooted runner tips growing freely (4). In the second experiment planting was done on October 13th, 2011 and final plant harvest was on April 16 th, 2012. Treatments were three source levels, respectively mother plants without defoliation, with one defoliation and two defoliations the four sinks levels as done in the first experiment. In both experiments, tips were collected and counted at the stage of one expanded leaf and/or visible root nodules, the crown diameter measured and dry mass determined. At the end of each experiment, mother plants were collected dry mass of roots, shoots and crown was determined. Shading reduced the number of runner tips produced by mother plants, total plant dry mass and the mean dry mass of tips when they were collected weekly and monthly while any effect was recorded on mother and daughter plants connected by stolons. The crown diameter of tips was not affected by shading the mother plants. The growth of mother plants was affected by shading and defoliation, but defoliation did not affect the emission of runner tips. It can be concluded that growth of mother plants might be reduced without affecting the emission of runner tips and the number of tips can be increased by keeping mother and daughter plants connected by stolons.